Early learners as health coaches for older adults preparing for surgery - Kaplan, Jennifer A (J Surg Res, 2016)
BACKGROUND: Few opportunities exist for early learners to engage in authentic roles on health care teams. In a geriatric optimization clinic for frail high-risk surgical patients, first year medical and nurse practitioner students were integrated into an interprofessional team as health coaches. MATERIALS AND METHODS: Frail surgical patients with planned operations were referred to a new pre-operative optimization clinic to see a geriatrician, occupational and physical therapists, and a nutritionist. A curriculum for health coaching by early learners was developed, implemented, and evaluated in this clinic. Students attended the clinic visit with their patient, reviewed the interdisciplinary care plan, called patients twice weekly preoperatively, and weekly in the first month after discharge. Students logged all calls, completed patient satisfaction surveys one week before surgery, and participated in feedback sessions with team members and medical school faculty. Call success rate was calculated and team communications were recorded and analyzed. RESULTS: Median call success rate was 69.2% and was lowest among medical students (p=0.004). Students and research assistants contacted or facilitated patient contact with their medical team 84 times. Overall, patients were extremely satisfied with the health-coach experience, felt better prepared for surgery, and would recommend the program to others. CONCLUSIONS: Early medical and nurse practitioner students can serve the important function of health coaches for frail patients preparing for surgery. Motivated students benefited from a unique longitudinal experience and gained skills in communication and care coordination. Not all students demonstrated capacity to engage in health coaching this early in their education.